2011
DOI: 10.1258/jms.2011.011086
|View full text |Cite
|
Sign up to set email alerts
|

Newborn screening for medium chain acyl-CoA dehydrogenase deficiency in England: Prevalence, predictive value and test validity based on 1.5 million screened babies

Abstract: BackgroundMedium chain acyl-CoA dehydrogenase deficiency (MCADD) is a rare, life-threatening condition. Early diagnosis by screening asymptomatic newborns may improve outcome, but the benefit to newborns identified with variants not encountered clinically is uncertain.ObjectiveTo estimate, overall and by ethnic group: screen-positive prevalence and predictive value (PPV); MCADD prevalence; proportion MCADD variants detected of predicted definite or uncertain clinical importance.SettingAll births in areas of hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 48 publications
4
34
1
1
Order By: Relevance
“…Importantly, it has been shown that the proportion of newborns with the prevalent c.985A>G homozygous genotype is approximately 50% in a screened population (Andresen et al 2012) as compared with 80% in a clinically presenting population (Tanaka et al 1992), supporting the notion that c.985A>G homozygous MCADD has a higher penetrance than most other MCADD genotypes. This is also reflected in the biochemical phenotype, where c.985A>G homozygous newborns have higher mean and median C8 carnitine levels than newborns with other ACADM genotypes (Andresen et al 2012;Oerton et al 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, it has been shown that the proportion of newborns with the prevalent c.985A>G homozygous genotype is approximately 50% in a screened population (Andresen et al 2012) as compared with 80% in a clinically presenting population (Tanaka et al 1992), supporting the notion that c.985A>G homozygous MCADD has a higher penetrance than most other MCADD genotypes. This is also reflected in the biochemical phenotype, where c.985A>G homozygous newborns have higher mean and median C8 carnitine levels than newborns with other ACADM genotypes (Andresen et al 2012;Oerton et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…MCADD presents with a characteristic acylcarnitine pattern that can easily be identified in dried blood spot samples by tandem mass spectrometry (Oerton et al 2011), and taken together with the excellent prognosis upon early treatment, MCADD is therefore part of the newborn screening (NBS) program in several countries. In Denmark, MCADD has been part of the NBS program since 2002 .…”
Section: Introductionmentioning
confidence: 99%
“…This contrasts with 42% of cases with two ACADM mutations and a genotype of "uncertain" significance ( Figure 1). [1]. The 'cut-off' shown for hexanoylglycine is empirical; the upper limit of normal by the method used was 1.1 micromol/mmol creatinine [5].…”
Section: To the Editormentioning
confidence: 99%
“…Sensitivity is high but specificity low. Homozygosity for the c.985A>G mutation is the most common genotype in MCADD in North-West Europe, constituting 80% of clinically-diagnosed cases in England but only 53% of screening-detected cases [1]. In a wider survey [2] only six of the 36 ACADM gene variants detected in screening-positive cases had also been identified in the clinically-presenting disorder making the presence of two variant alleles unsuitable as the sole diagnostic criterion.…”
Section: To the Editormentioning
confidence: 99%
See 1 more Smart Citation